Efeitos da exposição crônica ao organofosforado clorpirifós sobre a função cardiorespiratória - Batista, Thatiany Jardim (2018)
Previous studies of our group showed that acute exposure to high doses of organophosphorus compound (OP), chlorpyrifos (CPF), impaired cardiorespiratory reflexes in rats. In addition, some studies indicate that prolonged exposure to OP compounds impairs cardiovascular function, producing cardiac hypertrophy and altering the mechanical properties of the aorta. If prolonged CPF exposure also affects tonic and reflex cardiorespiratory function remained to be explored. Wistar rats were injected with CPF intraperitoneally (i.p.) for 4 weeks (three times a week) or 12 weeks (once a week) at the following doses: 7 mg/kg (CPF 7; 4 weeks, n=14; 12 weeks, n=14) and 10 mg/kg (CPF 10; 4 weeks, n=9; 12 weeks, n=12). The control group received saline (NaCl, 0.9%) for the same period (SAL, 4 weeks, n=9, 12 weeks, n=13). At the end of the treatment, the femoral artery and vein were catheterized under anesthesia with tribromoethanol (250 mg/kg, i.p.), to allow pressure recordings and drugs administration, respectively. After 24 hours of recovery from surgery, pulsatile arterial pressure (PAP) was recorded, from which diastolic blood pressure (DBP), systolic blood pressure (SBP), mean arterial pressure (MAP) and heart rate (HR) were derived. Respiratory rate (fR), tidal volume (VT) and minute volume (VE) were obtained by whole-body plethysmography. The chemorreflex responses were evaluated by intravenous injections of KCN (10, 20, 40 and 80 μg) while the spontaneous baroreflex was evaluated from the PAS and pulse interval (PI) recordings using the sequence method. These recordings were also used to evaluate heart rate variability (HRV) in time and frequency domain (spectral analysis). Finally, the activities of plasma acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) were also quantified. The results showed that the enzymatic activity of the CPF intoxicated animals was significantly lower than the control. In addition, CPF 10 group treated for 4 weeks presented a lower weight gain. No differences were observed in the baseline values of DBP, SBP, MAP, HR and fR, as well as in the HRV time-domain indices, either after 4 or 12 weeks of treatment. In the spectral analysis an increase was only observed for the very low frequency band (VLF). Animals treated with CPF presented an impairment of the baroreflex gain, for ascending ramps, and of the baroreflex effectiveness index (BEI). The chemoreflex bradycardic response was significantly reduced in the CPF treated rats for both treatment periods when compared to the control groups. No difference among groups was observed for the chemoreflex pressor response nor the tachypneic response for the two treatment periods. On the other hand, CPF 10 group had an increase in VT, for both treatment periods, and an increase in the VE, only after 1 month treatment. Similar to what was previously demonstrated after acute exposure to CPF, low doses chronic exposure also impairs cardiorespiratory function in rats. These results may have important clinical implications for workers, such as farmers, who are frequently exposed to these compounds.